2007
DOI: 10.1002/anie.200702036
|View full text |Cite
|
Sign up to set email alerts
|

Push–Pull Molybdenum Trisdithiolenes Allow Rapid Nonconventional Binding of Ethylene at Ligand Sulfur Atoms

Abstract: Adding to the mix: Mixed dithiolene complexes of molybdenum, such as [Mo{S2C2(CF3)2}2{S2(C6H4)}], bind ethylene rapidly, in a nonconventional fashion, at the sulfur atoms (see scheme). In the presence of additional donor ligands, substitution of the metal‐bound 2,3‐dihydro‐1,4‐dithiin occurs, providing a new approach to mixed‐ligand molybdenum bis‐ and trisdithiolenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 29 publications
1
40
0
Order By: Relevance
“…Using density functional theory (DFT), we found that both a pseudo-tetrahedral structure and the pyramidal structure that is relevant here are minima on the hypersurface for Mo(tfd) 2 , as confirmed by geometry optimization and subsequent frequency analysis (no imaginary frequency). The pyramidal structure (uphill relative to the pseudo-tetrahedral structure by 12.3 kcal/ mol) has two low-lying empty orbitals (LUMO and NLUMO), shown in Figure 4, that contain some p-orbital contribution from the sulfur atoms but are largely metalbased and correspond roughly to d x [24] [Mo(tfd) 2 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Using density functional theory (DFT), we found that both a pseudo-tetrahedral structure and the pyramidal structure that is relevant here are minima on the hypersurface for Mo(tfd) 2 , as confirmed by geometry optimization and subsequent frequency analysis (no imaginary frequency). The pyramidal structure (uphill relative to the pseudo-tetrahedral structure by 12.3 kcal/ mol) has two low-lying empty orbitals (LUMO and NLUMO), shown in Figure 4, that contain some p-orbital contribution from the sulfur atoms but are largely metalbased and correspond roughly to d x [24] [Mo(tfd) 2 …”
Section: Resultsmentioning
confidence: 99%
“…The most similar one is the ethylene adduct [Mo(tfd) 2 -{bdt(CH 2 CH 2 )}], with an average distance of 2.523 Å to the sulfur atoms on the dihydrobenzodithiin ligand. [24] The closest non-dithiolene-based Mo IV system is an octahedral molybdenum "S 4 -crown" thioether complex, with slightly shorter Mo-S(thioether) distances (2.469-2.498 Å). [28] Computed Mo-S distances for dht and tht bound to a Mo 3 S 9 catalyst model fragment are 2.53 Å and 2.50 Å, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[Mo(tfd) 3 ] or [Mo(bdt) 3 ] reacted with ethylene gave the corresponding 2,3-dihydro-1,4-dithiin derivative through a transient intraligand S,S 0 -cycloadduct. However, the mixed ligand tris(dithiolene) complex, [Mo(bdt)(tfd) 2 ] (4) or [Mo(bdt) 2 (tfd)], was reacted with ethylene and then the intraligand S,S 0 -cycloadduct (5) was successfully isolated (Chart 7(a)) [36]. This reaction is also explained by a molecular orbital overlap between dithiolene LUMO and alkene HOMO.…”
Section: 1 Formations Of Interligand and Intraligand Cycloadducts Bmentioning
confidence: 83%